A Novel Computational Approach for Calculating Sagittal Plane Urogenital Kinematics from Dynamic 2D Ultrasound - Czyrnyj, Catriona; Labrosse, Michel; McLean, Linda (CMBES Proceedings, 2016)
Up to half of women experience stress urinary incontinence (SUI) during tasks that increase intra-abdominal pressure. The exact biomechanics underlying urine leakage remains unclear, but is likely associated with concurrent failures in urethral sphincter function, urethral support, and pelvic floor muscle (PFM) mechanics. The biomechanics of the continence system during functional tasks can be assessed by transperineal ultrasound imaging (USI). However, during imaging, neither the USI probe nor the imaging surface is fixed in 3D space. With the pubic symphysis as the only bony landmark partially visible on sequential images, the impact of probe motion is difficult to assess. In practice, clinical researchers often compare measurements at rest to those at peak dynamic displacement without compensating for probe motion, and omit directionality despite its likely relevance. One proposed method of compensation defines a co-ordinate system with the origin set as the infero-posterior pubic symphysis and one axis running parallel to the urethra. However, we have noted substantial urethral deformation during dynamic tasks performed by many women with SUI, which has led us to question the validity of this approach. Instead, we have developed a new computational method to compensate for in-plane rotation and translation, allowing for more accurate calculation of urogenital kinematics during dynamic tasks known to cause urine leakage. We will present our computational method applied to the study of urogenital kinematics during dynamic tasks including voluntary PFM contraction, cough, and Valsalva maneuvers. The proposed approach may be used to comprehensively study the pathomechanics associated with SUI in women.